Penyuluhan dan Sosialisasi Pemanfaatan Kecerdasan Buatan dalam Kegiatan MICE dan Special Event pada Mahasiswa Pascasarjana Program Studi Pariwisata Universitas Pelita Harapan - Eko Prabowo; Kurniawan Gilang Widagdyo (Jurnal Relawan dan Pengabdian Masyarakat REDI, 2023)
As part of community service acitivity, the introduction and implementation of Artificial Intelligence (AI) in special events and the MICE (Meeting, Incentive, Convention, and Exhibition) industry have become important themes that can provide direct benefits to the community and the industry, particularly students as intellectual individuals. This activity takes the form of a presentation to postgraduate tourism students at Universitas Pelita Harapan, with the aim of providing in-depth insights to students and participants from event practitioner circles about how the application of AI technology in special events and the MICE industry can advance the industry and provide a better experience for participants. In this activity, the fundamental concepts of AI are elucidated to provide a strong understanding of the potential of this technology in aiding intelligent decision-making based on data. The use of AI technology in analyzing participant data in events enables the identification of trends and preferences, while personalizing participant experiences through content recommendations enhances interaction and engagement. The benefits of AI implementation in the MICE and events industry are outlined through improved operational efficiency, enhanced participant experiences, and the potential for innovation in event organization. This activity also acknowledges potential challenges, such as ethical considerations and data privacy and offers practical guidance on the implementation of AI in events and the MICE industry, providing participants with insights into initial steps that can be taken to adopt this technology. Through this approach, it is hoped that participants can form a better understanding of the benefits of AI, support industry development, and provide an improved experience for participants.